Exploratory phase II trial of an anti-PD-1 antibody camrelizumab combined with a VEGFR-2 inhibitor apatinib and chemotherapy as a neoadjuvant therapy for triple-negative breast cancer (NeoPanDa03): efficacy, safety and biomarker analysis - Xiaoxiao Liu; Chunying Zhuang; Lei Liu; Ling Xiong; Xin Xie; Ping He; Juanjuan Li; Bing Wei; Xi Yan; Tinglun Tian; Xiaorong Zhong; Jie Chen; et al. (Signal Transduction and Targeted Therapy)
Abstract Chemotherapy serves as the primary therapeutic approach for triple-negative breast cancer (TNBC), yet its efficacy remains unsatisfactory. This study was a single-arm, open-label, single-center clinical trial (NCT05447702) involving patients with newly diagnosed stage II-III TNBC at West China Hospital. The treatment regimen consisted of camrelizumab (200 mg intravenously every 2 weeks, 12 cycles), apatinib (250 mg orally daily), and alternating chemotherapy [nab-paclitaxel (d1, 8, 15 every 4 weeks) for 4 cycles and epirubicin plus cyclophosphamide (every 2 weeks) for 4 cycles]. From June 2023 to April 2024, 35 patients were enrolled, of whom 1 patient withdrew due to adverse reaction intolerance. At treatment completion, the total pathological complete response (tpCR, ypT0/is, ypN0) rate was 67.6% (23/34), and the breast pCR (ypT0/is) rate was 70.6% (24/34). The overall response rate following neoadjuvant treatment reached 94.1% (32/34). Elevated levels of alanine aminotransferase (38.2%) and aspartate aminotransferase (29.4%) were the most common grade 3-4 adverse events, with no significant toxicities or treatment-related deaths reported. Comprehensive analysis of serum and tissue samples collected before and after neoadjuvant therapy via Olink and RNA sequencing revealed that the treatment induced a complex systemic immune response. These findings enabled the development of two novel scoring systems: a pretreatment response predictive score system for stratification and an efficacy assessment score system for treatment response evaluation. In conclusion, camrelizumab and apatinib combined with chemotherapy have good clinical efficacy and good safety as neoadjuvant treatments for stage II-III TNBC, warranting further investigation and potential clinical application.